Psychological Wellbeing, Mindfulness, and Immunity of Teachers in Second or Foreign Language Education: A Theoretical Review - Li, Shengji (Frontiers in Psychology, 2021)
Teachers’ emotions and affective factors play quintessential roles in academic contexts as they influence almost all aspects of their profession. In an effort to provide a theoretical review of some teacher psychology constructs in this area, the current study has examined teachers’ psychological well-being, mindfulness, and immunity as three novel variables. More specifically, this article presents the definitions, dimensions, theories, and frameworks related to this domain drawing on positive psychology, complexity/dynamic systems theory, self-organization process, the reflexive self-consciousness theory, integrative awareness theories, and mindfulness framework. These theoretical underpinnings explain the constructs and the way they function in L2 education. Next, to provide evidence and justify the findings and propositions, empirical studies on each of the variables are reviewed. Finally, implications, research gaps, and suggestions for future inquiries are offered to interested researchers.